Knowledge, practices and restrictions related to menstruation in young girls: a study from North India - Sharma, Pallavi; Singh, Nilanchali; Tempe, Anjali; Sharma, Shalini (International Journal Of Community Medicine And Public Health, 2018)
Background: The aim of the study was to study the awareness, myths and menstrual practices in young girls in a tertiary care center. Methods: Predesigned structured questionnaire based study was done in 180 girls between the age group 13 to17 years, in the outpatient department of a tertiary care hospital in New Delhi. Informed consent was taken before filling up the questionnaire. Results: The participants were ignorant about the importance of proper hygiene and faced a lot restrictions related to daily life during their periods. 68% participants lacked adequate knowledge about the physiology of menstruation. 45% girls were informed regarding menstruation by mothers, sisters and friends whereas teachers played a limited role. 30% girls were using sanitary pads, while most were still using homemade cloths. Pads were being reused in every cycle and they were dried in damp places, preferably during night. Lack of awareness and appropriate care for menstrual morbidities was seen in these girls, which affects their educational attainment. Age old myths and practices still have a lot of impact on the Indian household. Conclusions: Ignorance and myths regarding menstruation still prevail in our society. The need of the hour is starting educational campaigns and schools based initiatives which can educate the girls. Thought should be given in manufacturing low cost sanitary pads as a national program. People especially in the rural set up should be encouraged to improve women’s social and reproductive health situation and counselling should be provided in relation to sanitation and disposal.